Chattering of proxy-based sliding mode control in the presence of parasitic dynamics - Ryo Kikuuwe (My University, 2021)
This paper reports an analysis on proxy-based sliding mode control (PSMC), which is a controller proposed by Kikuuwe & Fujimoto (2006, Proceedings of the 2006 IEEE International Conference on Robotics and Automation, pp. 25–30) originally for position control of robot manipulators. The describing function method is employed to investigate the chattering behavior of PSMC combined with a simple second-order plant with parasitic dynamics. The results show that PSMC is capable of achieving a lower tendency to chattering than the boundary-layer implementation of sliding mode control with the same sliding surface, without affecting the insensitivity to disturbance.
IMA Journal of Mathematical Control and Information
Keywords: Proxy-based; Parasitic dynamics; Campus Tijuana